Low back pain: a composite of interacting systems? - McGregor, Alison (Henry Stewart Talks, 2015)
Skeletal system: segmental joint motion of the spine, Muscular system: creating motion in body segments, Control system (CNS): co-ordination of muscles and body segments to produce function, Management and surgical care: surveys of practice, clinical studies and optimal post-operative management